Multifractal analysis of gas adsorption isotherms for pore structure characterization of the Bakken Shale - Liu, K.; Ostadhassan, M.; Zou, Jie; Gentzis, T.; Rezaee, M. Reza; Bubach, B.; Carvajal-Ortiz, H. (Elsevier Ltd, 2018)
Understanding pore heterogeneity can enable us to obtain a deeper insight into the flow and transport processes in any porous medium. In this study, multifractal analysis was employed to analyze gas adsorption isotherms (CO 2 and N 2 ) for pore structure characterization in both a source (Upper-Lower Bakken) and a reservoir rock (Middle Bakken). For this purpose, detected micropores from CO 2 adsorption isotherms and meso-macropores from N 2 adsorption isotherms were analyzed separately. The results showed that the generalized dimensions derived from CO 2 and the N 2 adsorption isotherms decrease as q increases, demonstrating a multifractal behavior followed by f(a) curves of all pores exhibiting a very strong asymmetry shape. Samples from the Middle Bakken demonstrated the smallest average H value and largest average a 10- -a 10+ for micropores while samples from the Upper Bakken depicted the highest average a 10- -a 10+ for the meso-macropores. This indicated that the Middle Bakken and the Upper Bakken have the largest micropore and meso-macropore heterogeneity, respectively. The impact of rock composition on pore structures showed that organic matter could increase the micropore connectivity and reduce micropore heterogeneity. Also, organic matter will reduce meso-macropore connectivity and increase meso-macropore heterogeneity. We were not able to establish a robust relationship between maturity and pore heterogeneity of the source rock samples from the Bakken.